Interaction between host genetics and drug therapy in influencing gut bacterial diversity - Magadze, Mulalo (Department of Pathology, 2026)
Background: Response to drug treatment shows inter-individual variability attributed mainly to environmental and genetic factors. It is now accepted that human genome variation and microbiome profiles play significant roles in patients' response to medication. This study aimed to investigate host genetic variation that affects an individual's microbiome profile and, ultimately, its effects on the therapeutic drug response of efavirenz (EFV) and warfarin. Efavirenz and warfarin are widely prescribed drugs for treatment of HIV and clotting disorders, respectively. Genetic polymorphisms in fucosyltransferase 2 (FUT2), Neural Cell Adhesion Molecule 1 (NCAM1), Shroom Family Member 3 (SHROOM3), Vitamin D receptor (VDR) and Lactase (LCT) were characterised and evaluated on their role on microbiome profiles and how this affected drug responses. Methods: Six hundred and forty-seven (n=647) African adults were recruited from Zimbabwe and blood for DNA extraction, stool samples for microbiome analysis and plasma for drug analyses were obtained. Genetic characterisation of SNPs, FUT2 (rs601338), NCAM1(rs17115310), SHROOM3 (rs11724031), VDR (rs1544410), VDR (rs7975232), VDR (rs731236), LCT (rs2164210) and LCT (rs7579771) was performed. Correlations were then made among genotypes and microbiome profiles on participants with different drug exposures (efavirenz and warfarin). Results: The five genes exhibited genetic variation. Baseline allele frequencies for each of the SNPs was as follows; FUT2 rs601338A (0.433), NCAM1 rs17115310G (0.233), SHROOM3 rs11724031A (0.192), VDR rs1544410T (0.255), VDR rs7975232C (0.270), VDR rs731236G (0.242), LCT rs2164210C (0.188) and LCT rs7579771T (0.292). The frequencies of the variant alleles showed differences when compared to other populations. FUT2 rs601338 was shown to have an influence on warfarin Cmax. Genera Actinomycetospora and Brevibacterium; and species Corynebacterium kroppenstedtii, Macrococcus caseolyticus and Kocuria kristinae were significantly abundant in the gut bacterial composition of FUT2 rs601338 AA genotype than the GG+GA genotypes. Bacterial order Bifidobacteriales were relatively abundant in the warfarin group iii than in the untreated control group whereas Symbiobacteriaceae was significantly plentiful in the efavirenz group than the untreated control group. Discussion: Genes that affect body colonising microbiomes, although not directly important in pharmacogenomics, influence treatment outcomes. There were some differences and similarities in the distribution of minor allele for the 8 variants studied when compared to other global populations, which could point to possible differences in microbiome profiles among individuals. Different microbiome profiles identified associated with the polymorphisms are likely to affect drug treatment outcomes, through host genetics, microbiome and drug interactions. Conclusion: These results show that African populations carry different polymorphisms which are likely to affect microbiome profiles and drug responses. Thus, when considering pharmacogenomics, it is important to take into account, microbiome profiles as these affect and are affected by therapeutic drugs.